2019
DOI: 10.31557/apjec.2019.2.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between safety management and patient safety culture in Cancer Treatment Centers

Abstract: Introduction: Enhancement of patient safety represents a principle objective followed by any health system, and it is necessary to consistently monitor the patient safety culture among nurses. Adopted by health service providers, the patient safety culture is described as the acceptance and maintenance of the patient safety as a common priority and value across the organization, or representation of the common patient safety-related values, beliefs, perceptions, and attitudes among the staff at centers providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Comparison of the risk level results showed that the major risk in the studied units was related to the dangers of inadequate cabling and placement of people in these work situations, which is consistent with similar studies [44]. The results of this study showed that educating workers will greatly reduce risk and is consistent with similar studies [38-45-46].The simultaneous use of training and work instructions, which is one of the outcomes and outputs of the Risk Assessment Operational Program (b, e and g), is one of the most important ways of controlling and reducing risks and enhancing staff safety knowledge and is consistent with similar studies [47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 88%
“…Comparison of the risk level results showed that the major risk in the studied units was related to the dangers of inadequate cabling and placement of people in these work situations, which is consistent with similar studies [44]. The results of this study showed that educating workers will greatly reduce risk and is consistent with similar studies [38-45-46].The simultaneous use of training and work instructions, which is one of the outcomes and outputs of the Risk Assessment Operational Program (b, e and g), is one of the most important ways of controlling and reducing risks and enhancing staff safety knowledge and is consistent with similar studies [47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 88%
“…Based on recent studies, the most important factor effecting the health state of the elderly, is stress and anxiety [11][12][13][14][15][16][17][18][19]. on the other hand stress is one of the most important risk factor that due to cancer [20][21][22][23][24][25][26][27][28]. In order to mitigate his issue, the causes of stress need to be identified, and counter measures need to be determined to improve their level of life expectancy and health.…”
Section: Presenting Approaches To Stress Management In the Elderly Inmentioning
confidence: 99%